Potensi Keterlibatan Multipihak dan Pendampingan Perguruan Tinggi berkelanjutan bagi Pengembangan Ekowisata Kapalo Banda dengan Daya tarik Utama Pembudidayaan Lebah Tanpa Sengat (Apidae: Meliponinae). - Henny Herwina; Mansyurdin; Syamsuardi; Jabang Nurdin; Muhammad Nazri Janra; Rita Maliza; Eli Ratni; Miftahul Ilmi; Nabilah Rahmachila Azura; Syakira Tiara Rezvi; Elni Fatimah; Fajri Hidayat; Jasmi; Dahelmi; Nofrita; Muhammad Idris; Putra Santoso; Jefrial Santoso (Warta Pengabdian Andalas, 2025)
The development of ecotourism in Kapalo Banda, Limau Manis, Padang, has potential to be expanded into agro-ecotourism through multi-stakeholder involvement. Key attractions include the scenic of river flows, agricultural cultivation, and stingless bee keeping, which support environmental sustainability and the local economy. With high vegetation diversity, the potential for stingless bee (galo-galo) breeding as a creative economic initiative offers new opportunities. This program aligns with the West Sumatra Provincial Government’s efforts to establish the area as a honey production center. However, challenges such as low colony production due to limited knowledge of farming techniques and the availability of flowering feed hinder its development. Through community engagement, empowerment activities were conducted from June to September 2024, including socialization, demonstrations, and training in bee farming techniques, supported by expert teams. Education focused on the potential of galo-galo and marketing strategies for local products. The results of this program indicate improved community skills and knowledge, supporting local economic sustainability and biodiversity conservation. Kapalo Banda partners have the potential to serve as a model for community empowerment based on natural resources, effectively enhancing community welfare. Multi-stakeholder involvement in developing Kapalo Banda Ecotourism has resulted in a series of activities ranging from cultivation preparation, colony propagation techniques, harvest preparation, to downstream processing and product marketing.